Notary Problems in Legal Counseling Regarding Marriage Contracts - Asy syifa, Asy syifa; Listyawati, Peni Rinda (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine the role of notaries in providing legal counseling to married couples regarding marriage agreements, identify the obstacles faced, and formulate solutions to improve the quality of legal counseling. This study uses a normative legal method with a descriptive qualitative approach and uses secondary materials through literature studies. The results of the study show that the implementation of the role and responsibilities of notaries in providing legal counseling to married couples regarding marriage agreements includes the entire series of initial consultations, counseling regarding content & procedures, drafting the deed with intensive communication, final reading and explanation, ensuring that the parties understand, obtain legal protection, and prevent potential disputes. The obstacles faced by notaries in carrying out legal counseling are due to the lack of legal literacy of married couples, local social and cultural stigma, limited time and administrative burdens, lack of socialization of the Constitutional Court decision No. 69 / PUU-XIII / 2015 regarding agreements that can be made after marriage. The solutions implemented by notaries to improve the effectiveness and quality of legal counseling to husbands and wives regarding marriage agreements include providing special time for consultations, collaborating with traditional/religious leaders and using local languages, conducting gradual pre-deed consultations, implementing digital services, and collaborating with the KUA/Dukcapil/Government. Keywords: Legal Counseling; Marriage Agreement; Notary; Roles and responsibilities.